BMP4 promotes SSEA‐1+ hUC‐MSC differentiation into male germ‐like cells in vitro. (13th June 2014) - Li, N.; Pan, S.; Zhu, H.; Mu, H.; Liu, W.; Hua, J.
Abstract Objectives Recent studies have demonstrated that primordial germ cells (PGC) can be differentiated from human umbilical cord mesenchymal stem cells (hUC‐MSCs), and embryonic stem cells (ESCs) in vitro. Nevertheless, efficiencies were low and unstable. Here, whether hUC‐MSCs can be induced to differentiate into germ‐like cells with the aid of bone morphogenetic protein (BMP4) was investigated. Materials and methods Human umbilical cord mesenchymal stem cells were freshly isolated and cultured with BMP4. SSEA‐1+/− cells were purified using magnetic‐activated cell sorting (MACS) from the hUC‐MSCs, and further induced with BMP4. Quantitative real‐time PCR (qRT‐PCR) and immunofluorescence analysis were used to determine PGC and germ‐like cell‐specific markers. Results Human umbilical cord mesenchymal stem cells differentiated into SSEA‐1+ spherical PGC‐like cells efficiently with 12.5 ng/ml BMP4. qRT‐PCR and immunofluorescence analysis demonstrated that SSEA‐1+ cells expressed higher levels of PGC‐specific markers than SSEA‐1− cells. Furthermore, SSEA‐1+ cells were induced with BMP4 to differentiate into STRA8, SCP3, DMRT1 and PLZF‐positive male germ‐like cells, and some sperm‐like cells were obtained by 7–14 days after induction. Conclusion These results suggest that SSEA‐1+ hUC‐MSCs can differentiate into male germ‐like cells in the presence of BMP4. This study provides an efficient protocol to study germ‐cell development using hUC‐MSCs.